CHEMICAL EVALUATION OF THE GENUS ACACIA OF PAKISTAN Part- V. Composition of Lipid Classes of Acacia cyanophylla Lindl., Acacia tortilis Hayne and Acacia victoriae Benth (Biological Sciences - PJSIR, 2022)
Seed lipids of Acacia cyanophylla Lind!. (9.8%), A. tortilis Hayne (6.0%) and J\. victoriae Benth. (5.3%) wereexamined for lipid classes and their fatty acid compositions. All the seed lipids were found to be rich in neutral lipids(64.1- 72.8%). Triglycerides constituted 75.4, 41.8 and 75.7% of the neutral lipids of Acacia cyanophylla, A. tortilis andA. victoriae respectively. The GC studies showed the presence of lauric (1.9, 0.0, 2.5%), myristic (2.8, 0.0, 1.2%),palmitic (22.1, 16.5, 18.3%), palmitoleic (3.6, 0.0, 2.5%), stearic (5.5, 8.2, 8.7%), oleic (30.4, 37.0, 36.5%), linoleic(29.1,32.9,20.5%), linolenic (2.8, 2.3,4.8%, arachidic (0.8, 1.0, 0.9%) and behenic acids (1.0, 2.1,4.1 %) in total lipidsof A. cyanopliylla, A. tortilis andA. victoriae respectively. The presence of lignoceric add was also observed in the seedlipids of A. cyanophylla.